Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Menggunakan Microsoft Powerpoint 2010 pada Materi Perbandingan Kelas VII - Izza Mafaza Rifqiyah Sayidi (Education Mind Based Development Association, 2022)
One of the obstacles to achieving the success of mathematical learning is the lack of utilization of media use during the learning process. Therefore, with the existence of interesting learning media can make it easier for students to understand the material. The goal of this research is to develop interactive multimedia-based learning media using Microsoft PowerPoint 2010 on comparison materials, and to find out the feasibility of such learning media. The type of research used is Research and Development or R&D. The procedures used are nine steps, i.e. looking for potential and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, and product revisions. The subject of this study was a class VII student at MTs. Hasan Kafrawi 2 which amounted to 45 students. The data collection technique used is the questionnaire. Then the data obtained will be analyzed to find out the feasibility of the product. The results showed that after a test of the use by 45 students showed an average score of 89,178 then this learning media included to the category